Natural Antioxidants can Improve Microplastics-Induced Male Reproductive Impairment in the African Catfish (Clarias Gariepinus) - El-Din H. Sayed, Alaa; Hamed, Mohamed; Ismail, Rania F. (Frontiers in Environmental Science, 2022)
This study was conducted to explore the protective potential of three different antioxidant supplements, lycopene, citric acid, and Chlorella, against reproductive injuries induced by microplastics (MPs) in freshwater mature male catfish. A total of 150 mature male African catfish (Clarias gariepinus) were assigned to five treatment groups as follows: control group fish were fed with control diet, the second group fish were fed with 500 mg/kg MP diet, and the remaining three groups of fish were fed with 500 mg/kg MP diet plus lycopene (500 mg/kg diet), citric acid (30 g/kg diet), and Chlorella (50 g/kg diet), respectively, for 15 days. Ingestion of MPs significantly decreased serum luteinizing hormone, follicle-stimulating hormone, sex steroid (testosterone and estradiol) levels and sperm count, spermatocrit, motility, and viability. It also induced histological alterations and degenerative changes in testicular tissues. Administration of lycopene and Chlorella with MP diets maintained hormone levels comparable to those in the control group, enhanced sperm quality, and decreased testicular histological damage. Chlorella was more effective in enhancing sperm quality, and lycopene was more efficient in alleviating testicular tissue damage. Citric acid supplementation was irrelevant in mitigating MP-induced injury. This study indicated that both lycopene and Chlorella ameliorated the MP-induced reproductive dysfunction by improving reproductive hormonal levels, sperm parameters, and histological configuration, whereas the citric acid dose used in this study was not effective in ameliorating the MP-induced reproductive stress. Additional research and monitoring of MP-induced pollution in freshwater ecosystems are required to avoid the severity of reproductive toxicity in freshwater fish.